2015
DOI: 10.2166/aqua.2015.117
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ripening time of full-scale manganese removal filters with manganese oxide-coated media

Abstract: Effective manganese removal by conventional aeration-filtration with virgin filter media requires a long ripening time. The aim of this study was to assess the potential of manganese oxide-coated media to shorten the ripening time of filters with virgin media, under practical conditions. A full scale filter filled with virgin sand and a full scale filter filled with anthracite/sand were operated at two groundwater treatment plants, in parallel with (full scale) test filters, with an additional layer of Mangane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…If the water contains aggressive carbon dioxide, pH could be increased by using calcium carbonate filter media (Cox, 1933). Alternatively, utilities could consider using filter media pre-coated in Mn (oxyhydr)oxides to encourage heterogeneous Mn removal (Bruins et al, 2015b).…”
Section: Relationship Between Predicted Mn Mineral Formation and Mnmentioning
confidence: 99%
“…If the water contains aggressive carbon dioxide, pH could be increased by using calcium carbonate filter media (Cox, 1933). Alternatively, utilities could consider using filter media pre-coated in Mn (oxyhydr)oxides to encourage heterogeneous Mn removal (Bruins et al, 2015b).…”
Section: Relationship Between Predicted Mn Mineral Formation and Mnmentioning
confidence: 99%
“…In chemically coated filter media, the carrier dominates quantitatively over the coating and it has been shown that for this type of materials it is better to compare adsorption capacity in terms of unitary value of specific surface area [144]. Bruins et al [145] considered this need when comparing filter media of varying density and proposed a reference to the unitary volume of material. As shown in the data presented in Table 2, the amount of MnO x deposited on a mineral support is varied and most often ranges from a few tenths to several mg/g of coated filter media.…”
Section: Adsorption Propertiesmentioning
confidence: 99%
“…In the start-up period, the filter slowly achieves higher and higher treatment efficiency until satisfactory results are obtained. The duration of this period varies and depends on many factors, such as chemistry of groundwater, technological conditions of water filtration, filter design, and properties of the filter medium, implies a rate of ripening [31,145]. A summary of information on this topic is provided in Table 5.…”
Section: Coating Formationmentioning
confidence: 99%
“…7 In addition, the manganese oxides (MnO x ), formed by these processes, gradually cover the filter medium, contributing to the removal of Mn through auto-catalytic adsorption and subsequent oxidation of adsorbed Mn by biological and/or physicochemical means. 8,9 At the end of the start-up period, efficient and stable removal of Mn is expected. 10 The length of this period is potentially influenced by the type and amount of manganese oxide coated in the filter medium, 11 the quality of the raw water, and some operational or design aspects such as the volumetric loading of iron, the backwashing strategy, and the type of filter medium.…”
Section: Introductionmentioning
confidence: 99%
“…10 The length of this period is potentially influenced by the type and amount of manganese oxide coated in the filter medium, 11 the quality of the raw water, and some operational or design aspects such as the volumetric loading of iron, the backwashing strategy, and the type of filter medium. 8,12 The attachment of bacteria to the filter medium is a physicochemical process that can be influenced by the texture, the properties of the surface, the accessible areas of the support medium, 13 and the water temperature. 14 Microbial colonization would increase as the surface roughness of the filter media increases, as shear forces decrease and the surface area increases.…”
Section: Introductionmentioning
confidence: 99%